Assessment the Changing Trend of Susceptibility to Two Insecticides Among Field-Population Culex quinquefasciatus Compared with the Same Population Undergoing to Multiple Colonization - Atieh Shemshadian; Mohammad Reza Abai; Hassan Vatandoost; Navid Dinparast-Djadid; Mohammad Ali Oshaghi; Abdolrasoul Mojahedi (Tehran University of Medical Sciences, 2020)
Background: During the past decade, rapid development of insecticide resistance have been reported among many species of mosquito vectors against four main categories of insecticides worldwide. The aim of the research was to assess the variation trend of susceptibility levels of Culex quinquefasciatus to two insecticides separately for the field population compared with subsequent generations of the same sample after multiple colonization. Methods: Larvae and pupae of Cx. quinquefasciatus were collected from house sewages and reared to adult which blood-fed on roosters. Ten percent sucrose fed female mosquitoes aged 2-3 days were used for susceptibility tests with DDT and deltamethrin. Susceptibility levels was assessed in the adult stage of field stran Cx. quinquefasciatus against DDT 4.0% and deltamethrin 0.05% and continued up to next six generations undergoing multiple rearing at insectary condition. Results: The susceptibility levels to DDT 4.0% did not change compared to the field with the lab population to six generations. Regarding deltamethrin 0.05%, no significant difference was shown between field strain (58.3%) and 3rd generation (52.7%) compared to the 6th one (33.8%). Conclusion: This finding may reflect the role of the kdr gene in resistance to organochlorine which has cross-resistance with pyrethroid insecticides. The results of this study clearly showed the irreversible trend of pyrethroid resistance among colonized mosquitoes. This is the first study of the resistance status of Cx. quinquefasciatus in Iran.